Hubungan Karakter Berdemokrasi dan Hasil Belajar PKn di MAN 2 Kandangan - Jamaludin, Muhammad (Jurnal Pendidikan Kewarganegaraan, 2015)
Democratization character was developed with a new paradigm about involvement of students in the learning process, that is not only active in the learning process, but they are also given the opportunity to determine the learning activities they will do, together with their teachers who have all the forms of a positive relation between the perception of the character with learning results of students. Character education priorities embedded in school of MAN 2 Kandangan reflected in the learning process applied by civics teacher who strongly supports the establishment of a democracy character. The purpose or this reseacrh are : (1) to describe character of student in democracy in MAN 2 Kandangan; (2) to know civics learning results in MAN 2 Kandangan; and (3) to know relation between democracy character and civics learning results in MAN 2 Kandangan.Research method using quantitative descriptive approach with colleration method. The research population wa all students of the class. Population in this research were students of class X and XI of MAN 2 Kandangan which amounts to 372 are 181 smples. Collection data using questionnaires. Data analysis with colleration using Pearson Product Moment formula with SPSS version 16.The results of this research show that: (1) democracy character of the civics in school of MAN 2 Kandangan quite well, and high, where students uphold democracy character well in envirinment of school and society; (2) civicsÂ  learning result in MAN 2 Kandangan quite well with the average 75,98; and (3) Be found a relation between democracy character and civics learning results in MAN 2 Kandangan where based on test resultsr calculated (0,396) > r table (0,148). So, it can be concluded that colleration coefficient for 0,396 is significant, which means that be found a relation between the variable X (democracy character) and the variable Y (civics learning results).Keywords: Relation, Demokracy Character, Civics, Learning Results